BUILDING INFORMATION MODELLING IN CONSTRUCTION: CHALLENGES AND IMPROVEMENT OF FACILITIES MANAGEMENT - Norpadzlihatun Manap; Jasmine Lye Loke Hong; Noralfishah Sulaiman; Fatema Ali Saeed Taffoof Alshehhi; Chen Jingzhi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This research aims to investigate the challenges of BIM adoption in facilities management and suggest improvements in facilities management. Interview sessions were conducted with six construction experts who have been construction experts in the construction field for at least ten years. The research collected several challenges to the adoption of BIM in facilities management, which include limitations in the adoption of BIM in facilities management and integration of BIM to transfer information and data to the facilities maintenance stage. The improvements suggested by the respondents were converting the facilities management process, which currently is manual, into a digital tool, and cultivating BIM talents and BIM teams,